Work-related health factors among female immigrants in Sweden - A qualitative study on a sample of twenty workers (Italian Journal of Public Health, 2006)
Aims: The purpose of this study was to explore work-related health factors amongst female immigrants in Sweden.Methods: Qualitative methods were used in order to get the broadest possible picture of female immigrants’ perceptions on work-related health factors. Semi-structured interviews were conducted with twenty female immigrants who worked in different departments of a municipality adjacent to a large city in Sweden. Most of the interviewed women came from the Middle East, Africa and Latin America, while some came from eastern and southern Europe as well as Finland. The women had lived in Sweden for 5-27 years. Content analysis, which is based on analysis by topic, was used to analyse the data.Results: Results from the interviews show that female immigrants perceived that work-related health is strongly associated with class. The three aspects of class that arose from this study were wage, professional status and their position within the organisations hierarchy. Other factors that were identified as being associated to work-related health were discrimination due to ethnicity and gender, unfavourable physical and psychosocial work environment and lack of training opportunities for upgrading their skills.Conclusions: The public health implications of the findings in this study suggest that measures that ought to be taken to improve female immigrants working conditions and health are primarily systematic efforts to counteract discrimination because of gender and ethnicity in areas such as wage setting and opportunities for skill up-grade training. This should result in improved employment opportunities for female immigrants, particularly those who work in low status and low-paid jobs.
Keywords: Work; health; emale immigrants; class; discrimination